Social Media Approach To Crisis Communication During Covid-19 Pandemic: An Analysis From Malaysian Perspective - Rosninawati Hussin; Suria Hani A. Rahman; Norizzati Azudin (USIM PRESS, 2024)
Vol. 33 No. S5 (2021): ULUM ISLAMIYYAH The Malaysian Journal of Islamic Sciences